Implementation of Speech Engineering in Android Application using Chess Game - Nurhadi Sukmana; Lupita Citra Astari (IT for Society, 2016)
Nowadays, almost all people have smartphone as one of their needs for their social life. Although the main function of smartphone is to communicate easier with others, it doesn’t close the possibility for the phone to be ‘smart’, which is have another functions beside that. From smartphone, human can develop their skills, mostly soft skills anytime and anywhere.